2000
DOI: 10.1080/00224540009600475
|View full text |Cite
|
Sign up to set email alerts
|

Learning Achievement, Social Adjustment, and Family Conflict Among Bedouin-Arab Children From Polygamous and Monogamous Families

Abstract: A sample of 146 Bedouin-Arab pupils from polygamous and monogamous families participated in this study, which was conducted in a Bedouin-Arab village in the Negev, Israel. The authors compared learning achievement, social adjustment, and family conflict. Data revealed differences between the two groups: The children from monogamous families had higher levels of learning achievement than did the children from polygamous families; in addition, those from monogamous families adjusted to the school framework bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 24 publications
1
57
2
Order By: Relevance
“…This review provided no evidence to support this suggestion. The few studies that focussed on younger children (e.g., Al-Krenawi & Lightman, 2000) found a similar pattern of results to those of adolescents. Given the paucity of cross-sectional studies comparing age groups or longitudinal studies considering effects over time, we agree with Elbedour et al (2000) that the impact of polygamy across the course of development requires further empirical attention.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…This review provided no evidence to support this suggestion. The few studies that focussed on younger children (e.g., Al-Krenawi & Lightman, 2000) found a similar pattern of results to those of adolescents. Given the paucity of cross-sectional studies comparing age groups or longitudinal studies considering effects over time, we agree with Elbedour et al (2000) that the impact of polygamy across the course of development requires further empirical attention.…”
Section: Discussionmentioning
confidence: 54%
“…Three studies reported that family income and/or parental employment was lower in polygynous than monogamous families (Al-Krenawi et al, 2002;Al-Krenawi & SlonimNevo, 2008, Hamden et al, 2009, two reported no differences in the range of occupations (Al-Krenawi & Lightman, 2000;Bamgbade & Saloviita, 2014) and the remaining 8 papers did not report extractable information to compare family income/occupations. This lack of consistency in reports of parental education and income creates difficulties for proposing these variables as influential variables for child and adolescent outcomes.…”
Section: Cultural Context and Demographic Variablesmentioning
confidence: 99%
See 3 more Smart Citations